2004
DOI: 10.1038/sj.bjc.6602255
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β1 is required for the invasive behaviour but not proliferation of squamous cell carcinoma cells in vivo

Abstract: Integrin b1 is both overexpressed and in an 'active' conformation in vulval squamous cell carcinomas (VSCCs) compared to matched normal skin. To investigate the significance of integrin b1 deregulation we stably knocked-down integrin b1 expression in the VSCC cell line A431. In vitro analysis revealed that integrin b1 is required for cell adhesion, cell spreading and invasion. However, integrin b1 is not required for cell growth or activation of FAK and ERK signalling in vitro or in vivo. Strikingly, while con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 38 publications
6
60
0
Order By: Relevance
“…In particular, silenced cells embedded into the 3D matrigel/collagen I matrix organize in spheroids smaller than control ones (data not shown), that do not extend protrusions, whereas control cells give rise to sprouted structures. Consistently, also in the squamous carcinoma A431 cells, b1 integrin silencing gave rise to less invasive tumors (Brockbank et al, 2005). Although we were unable to perform lung colonization assays with the A549 cells, these in vitro data already clearly support the primary role of b1 integrin in regulating lung cancer cell motility.…”
Section: Discussionsupporting
confidence: 74%
“…In particular, silenced cells embedded into the 3D matrigel/collagen I matrix organize in spheroids smaller than control ones (data not shown), that do not extend protrusions, whereas control cells give rise to sprouted structures. Consistently, also in the squamous carcinoma A431 cells, b1 integrin silencing gave rise to less invasive tumors (Brockbank et al, 2005). Although we were unable to perform lung colonization assays with the A549 cells, these in vitro data already clearly support the primary role of b1 integrin in regulating lung cancer cell motility.…”
Section: Discussionsupporting
confidence: 74%
“…Previous work showed that LAMC2 binds to integrin α2/β1, 34 and integrin is required for invasion in some tumors. 35 To test whether integrin participates in LAMC2-induced EMT, we first assessed the potential interaction between LAMC2 and integrin in NSCLC cells. LAMC2 pulldown experiments showed that both endogenous and exogenous LAMC2 interacted with integrin β1 in H2122, PC9, and A549R4 cells (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
“…However, b1-integrin-blocking antibodies induced a morphological and functional reversion of tumoral phenotype (Weaver et al, 1997) and blocked the proliferation (Wang et al, 2002) in breast cancer cells. In vulva squamous carcinomas, b1-integrin is overexpressed and required for the invasive pattern (Brockbank et al, 2005). Interestingly, post-transcriptional modification of b1-integrin contributes to colon cancer progression (Seales et al, 2005).…”
Section: Discussionmentioning
confidence: 99%